Potential for Biocontrol of Hairy Root Disease by a Paenibacillus Clade - Bosmans, Lien; De Bruijn, Irene; Gerards, Saskia; Moerkens, Rob; Van Looveren, Lore; Wittemans, Lieve; Van Calenberge, Bart; Paeleman, Anneleen; Van Kerckhove, Stefan; De Mot, René; Rozenski, Jef; Rediers, Hans; et al. (Frontiers in Microbiology, 2017)
Rhizogenic Agrobacterium biovar 1 is the causative agent of hairy root disease (HRD) in the hydroponic cultivation of tomato and cucumber causing significant losses in marketable yield. In order to prevent and control the disease chemical disinfectants such as hydrogen peroxide or hypochlorite are generally applied to sanitize the hydroponic system and/or hydroponic solution. However, effective control of HRD sometimes requires high disinfectant doses that may have phytotoxic effects. Moreover, several of these chemicals may be converted to unwanted by-products with human health hazards. Here we explored the potential of beneficial bacteria as a sustainable means to control HRD. A large collection of diverse bacterial genera was screened for antagonistic activity against rhizogenic Agrobacterium biovar 1 using the agar overlay assay. Out of more than 150 strains tested, only closely related Paenibacillus strains belonging to a particular clade showed antagonistic activity, representing the species P. illinoisensis, P. pabuli, P. taichungensis, P. tundrae, P. tylopili, P. xylanexedens and P. xylanilyticus. Assessment of the spectrum of activity revealed that some strains were able to inhibit the growth of all 35 rhizogenic agrobacteria strains tested, while others were only active against part of the collection, suggesting a different mode of action. Preliminary characterization of the compounds involved in the antagonistic activity of two closely related Paenibacillus strains, tentatively identified as P. xylanexedens, revealed that they are water-soluble and have low molecular weight. Application of a combination of these strains in greenhouse conditions resulted in a significant reduction of HRD, indicating the great potential of these strains to control HRD.